2022
DOI: 10.1021/acsami.2c19224
|View full text |Cite
|
Sign up to set email alerts
|

Washable and Breathable Electret Sensors Based on a Hydro-Charging Technique for Smart Textiles

Abstract: Flexible electromechanical sensors based on electret materials have shown great application potential in wearable electronics. However, achieving great breathability yet maintaining good washability is still a challenge for traditional electret sensors. Herein, we report a washable and breathable electret sensor based on a hydro-charging technique, namely, hydro-charged electret sensor (HCES). The melt-blown polypropylene (MBPP) electret fabric can be charged while washing with water. The surface potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In detail, due to the excellent porous network structure, the fabric electrode has the highest permeability of 1161 mm s –1 ; after compositing with IL, the permeability of the fabric electrolyte decreases to 455.3 mm s –1 , and when assembled, the fabric sensor device shows a permeability of 224.9 mm s –1 , which is still much higher than that of nylon (∼79.1 mm s –1 ) and TPU film (∼34.2 mm s –1 ). Furthermore, Table S2 compares the air permeability between the fabric sensor developed in this work and those reported in the literature, ,, indicating that the excellent permeability is achieved in the field. It is also found that the permeability of the sensor is positively influenced by the applied air pressure (Figure b).…”
Section: Resultsmentioning
confidence: 69%
“…In detail, due to the excellent porous network structure, the fabric electrode has the highest permeability of 1161 mm s –1 ; after compositing with IL, the permeability of the fabric electrolyte decreases to 455.3 mm s –1 , and when assembled, the fabric sensor device shows a permeability of 224.9 mm s –1 , which is still much higher than that of nylon (∼79.1 mm s –1 ) and TPU film (∼34.2 mm s –1 ). Furthermore, Table S2 compares the air permeability between the fabric sensor developed in this work and those reported in the literature, ,, indicating that the excellent permeability is achieved in the field. It is also found that the permeability of the sensor is positively influenced by the applied air pressure (Figure b).…”
Section: Resultsmentioning
confidence: 69%
“…At the same time, in order to test the washability of the fibrous multifunctional sensor, we conducted a performance test on the sensor after several washes. 59–62 The pictures before and after cleaning and the performance test results are shown in Fig. S5 †.…”
Section: Resultsmentioning
confidence: 99%
“…[35] Therefore, a Braille-to-speech translation system comprising of all-textile tactile sensors and loudspeakers with high performances and a facial fabrication process is in high demand. Textile integrated electrostatic transducers (ETs), based on the electrostatic induction effect, have been developed to serve as tactile sensors, [36][37][38] energy harvesters, [39][40][41] flexible microphones, [42] and soft actuators [43][44][45] due to their flexibility, lightweight, excellent output performance, and comfortability. For instance, a textile ET fabricated with conductive yarn and nylon yarn can achieve high-pressure sensitivity of 7.84 mV Pa −1 and excellent machine washability.…”
Section: Introductionmentioning
confidence: 99%